Logit ve probit modellerinde uyum iyiliği ölçüleri - (:unkn) unknown (My University, 2010)
Bu çalışmada, farklı uyum iyiliği ölçülerinin hesaplanması ve hem logit hem de probit model için sonuçlarının karşılaştırılması amaçlanmıştır. Çalışma sonucunda elde edilen bulgular incelendiğinde, farklı uyum iyiliği ölçülerinin farklı sonuçlar verdiği görülmüştür. Sonuçlar göstermektedir ki; modellerin karşılaştırılması için aynı uyum iyiliği ölçüsünün hesaplanması ve kullanılması oldukça önemlidir.

In this paper, we calculate the different goodness of fit measures for both logit and probit model and compare the results. The findings of the study indicate that there are large numerical differences between the different measures. The results show that it is obviously important to ensure it is the same measure when comparing the goodness of fit values from the same estimation method on different data sets and models.
Goodness of fit measures in logit and probit